PERAMALAN HARGA MATA UANG KRIPTO SOLANA MENGGUNAKAN METODE SUPPORT VECTOR REGRESSION (SVR) - Dewi Marini Umi Atmaja; Arif Rahman Hakim (Jurnal Media Elektro, 2022)
Cryptocurrencies have great potential to be adopted in Indonesia as an alternative to investing. One of the cryptocurrencies that investors or traders are interested in is Solana. Fluctuating price. movements make cryptocurrency investments considered. speculative so the risks. faced are very high. With this, we need a system or model that can help investors or traders to predict prices so that investors or traders have material for consideration in making decisions. The results of the descriptive analysis can be seen that in the period from April 10, 2020 to May 30, 2022, Solana's daily closing price movement fluctuates. The Support Vector Regression model obtained for Solana's daily closing price data, namely the Linear kernel with cost parameter C = 1000, obtained an. accuracy of 97.44% and MAPE 9.93 while for the Radial Basis Function. (RBF) kernel with cost parameter C = 1000 an .gamma = 0.1 obtained an accuracy of 87.76% with a MAPE value of 8.14. It can be concluded that through parameter tuning, the model formed has an accuracy value and the. best MAPE is to use a linear kernel with a cost parameter of C = 1000.